2010
DOI: 10.1121/1.3257211
|View full text |Cite
|
Sign up to set email alerts
|

Broadband source localization using horizontal-beam acoustic intensity striations

Abstract: Waveguide invariant theory is applied to horizontal line array (HLA) beamformer output to localize moving broadband noise sources from measured acoustic intensity striation patterns. Acoustic signals emitted by ships of opportunity (merchant ships) were simultaneously recorded on a HLA and three hydrophones separated by 10 km during the RAGS03 (relationship between array gain and shelf-break fluid processes) experiment. Hough transforms are used to estimate both the waveguide invariant parameter "beta" and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 15 publications
0
29
0
2
Order By: Relevance
“…Some of these methods include matched field processing which attempts to maximize an objective function which correlates the modeled and measured acoustic fields (Bucker, 1976;Baggeroer et al, 1988;Fawcett et al, 1996); modal decomposition methods which seek to match the modeled and measured modal amplitudes as a function of depth (Shang, 1985;Yang, 1987;Glattetre et al, 1989); matched mode methods which endeavor to match modeled and observed mode amplitudes as measured on a horizontal line array by use of the frequency-wavenumber (f-k) transform (Nicolas et al, 2006); and waveguide invariant approaches which are based on Chuprov's (1982) parameterization relating range and frequency to the slope of the striations in acoustic pressure in a frequency-range plot (Brekhovskikh and Lysanov, 1991;D'Spain and Kuperman, 1999). The waveguide invariant is commonly interpreted in terms of constructive and destructive interference of propagating normal modes (Turgut and Orr, 2010), but it has also been described in terms of ray theory (Gerstoft et al, 2001) and variations in eigenray arrival times (Harrison, 2011), and related to the wavenumber integration technique (Cockrell and Schmidt, 2010). Upon close inspection, the current technique can be loosely interpreted to be a dimensionally-reduced form of both the waveguide invariant process (WIP) and the mode matching method (MMM) using the f-k representation mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these methods include matched field processing which attempts to maximize an objective function which correlates the modeled and measured acoustic fields (Bucker, 1976;Baggeroer et al, 1988;Fawcett et al, 1996); modal decomposition methods which seek to match the modeled and measured modal amplitudes as a function of depth (Shang, 1985;Yang, 1987;Glattetre et al, 1989); matched mode methods which endeavor to match modeled and observed mode amplitudes as measured on a horizontal line array by use of the frequency-wavenumber (f-k) transform (Nicolas et al, 2006); and waveguide invariant approaches which are based on Chuprov's (1982) parameterization relating range and frequency to the slope of the striations in acoustic pressure in a frequency-range plot (Brekhovskikh and Lysanov, 1991;D'Spain and Kuperman, 1999). The waveguide invariant is commonly interpreted in terms of constructive and destructive interference of propagating normal modes (Turgut and Orr, 2010), but it has also been described in terms of ray theory (Gerstoft et al, 2001) and variations in eigenray arrival times (Harrison, 2011), and related to the wavenumber integration technique (Cockrell and Schmidt, 2010). Upon close inspection, the current technique can be loosely interpreted to be a dimensionally-reduced form of both the waveguide invariant process (WIP) and the mode matching method (MMM) using the f-k representation mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…(In a practical situation, one would likely plot |Υ total (ω, θ L , θ S ; w)| 2 versus snapshot number and ω while changing θ L with the snapshot number to follow the source, and then estimate the range and speed of the source. See [62]. )…”
Section: Hla Response To Source In Waveguidementioning
confidence: 99%
“…The output of the beamformer will contain striations that are almost the same as the striations present in the single-hydrophone acoustic intensity, while rejecting noise coming from directions other than that of the source of interest. In [62], Turgut et al used the methods described in [66] to successfully localize an acoustic source with experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations